Rapid Landscape Changes in Plastic Bays Along the Norwegian Coastline - Bastesen, Eivind; Haave, Marte; Andersen, Gidske L.; Velle, Gaute; Bødtker, Gunhild; Krafft, Charlotte Gannefors (Frontiers in Marine Science, 2021)
The Norwegian Coastal Current transports natural debris and plastic waste along the Norwegian coastline. Deposition occurs in so-called wreck-bays and includes floating debris, such as seaweed, driftwood and volcanic pumice, and increasing amounts of plastics during the last decades. Deposition in these bays is controlled by ocean currents, tidal movements, prevailing winds and coastal morphology. We have compared soil profiles, analyzed the vegetation and inspected aerial photos back to 1950 in wreck-bays and defined three zones in the wreck-bays, where accumulation follows distinct physical processes. Zone 1 includes the foreshore deposition and consists of recent deposits that are frequently reworked by high tides and wave erosion. Thus, there is no accumulation in Zone 1. Zone 2 is situated above the high tide mark and includes storm embankments. Here, there is an archive of accumulated debris potentially deposited decades ago. Zone 3 starts above the storm embankments. The debris of Zone 3 is transported by wind from Zone 1 and Zone 2, and the zone continues onshore until the debris meets natural obstacles. Plastic accumulation seems to escalate soil formation as plastic is entangled within the organic debris Mapping and characterizing the soil layers indicates that deep soils have been formed by 50 or more years’ accumulation, while the pre-plastic soil layers are thin. The plastic soil forms dams in rivers and wetlands, changing the shape and properties of the coastal landscape, also altering the microhabitat for plants. This case-study describes an ongoing landscape and vegetation change, evidently co-occurring with the onset of plastic accumulation. Such processes are not limited to the Norwegian coastline but are likely to occur wherever there is accumulation of plastic and organic materials. If this is allowed to continue, we may witness a continued and escalating change in the shape and function of coastal landscapes and ecosystems globally.